Vitamin D concentration in maternal serum during pregnancy: Assessment in Hokkaido in adjunct study of the Japan Environment and Children's Study (JECS). - Ko Nakanishi; Mami Mutoh; Sachiko Itoh; Sumitaka Kobayashi; Takeshi Yamaguchi; Hiroyoshi Iwata; Naomi Tamura; Momoko Koishi; Machiko Kasai; Emi Kikuchi; Nanae Yasuura; Reiko Kishi; et al. (PLoS ONE, 2024)
Background Vitamin D is an essential nutrient for maintaining blood calcium and phosphorus levels and controlling bone density. Deficiency in it leads to rickets, osteomalacia, osteoporosis, and various other diseases. Recently, it has gained attention for reportedly reducing the risk of COVID-19 severity. However, there are no reports evaluating pregnant women in the Hokkaido region of Japan. This study aims to elucidate the current status of vitamin D levels in pregnant women in the Hokkaido region. Methods This study measured the serum concentrations of Vitamin D2 and D3 in 206 pregnant women participating in the Japan Environment and Children's Study-Hokkaido sub-cohort at the Hokkaido Regional Center. It analyzed the relationship between these concentrations and the months, seasons, and sunshine hours. Results The mean maternal age was 31.7 ± 4.7 years, and the mean prepregnancy BMI was 21.0 ± 2.5 kg/m2. Only two women have given birth at least once. Regarding sunscreen use, 65 participants (31.6%) responded "often" or "sometimes." Five women used the supplement containing Vitamin D. The value of 25(OH)D2 was above 1 ng/ml in four of them. The average 25(OH)D3 level was 12.1 ng/ml, with a median of 11.0 ng/ml. Four participants (1.9%) had levels below 5 ng/ml. The highest median of 25(OH)D3 was in July, and the lowest was in April. The concentration of 25(OH)D3 was significantly higher in summer than in winter. A correlation was found between 25(OH)D3 and sunshine hours, with 25(OH)D3 concentrations gradually increasing as sunshine hours increase. Conclusion It was found that almost all pregnant women in Hokkaido were deficient in vitamin D. It is necessary to implement measures to enhance vitamin D levels in pregnant women to safeguard the health of women and fetuses in Hokkaido.